2018
DOI: 10.3390/su10030857
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Ecosystem Service Bundles to Detect Distinct Types of Multifunctionality within the Diverse Landscape of the Yangtze River Basin, China

Abstract: Abstract:The tradeoffs and synergies of ecosystem services are widely discussed and recognized. However, explicit information for understanding and managing the complex relationships of multiple ecosystem services at regional scales is still lacking, which often leads to the degradation of important ecosystem services due to one ecosystem service being enhanced over another. We assessed the biodiversity and the production of nine ESs (ecosystem services) across 779 counties in the Yangtze River Basin, the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Areas with the best agricultural soils were also identified as locations with specialised bundles -for instance, a study in Quebec by Renard et al (2015) showed that good soils were locations of bundles with a low diversity of services and dominated by crop production. Another study, in the Yangtze River Basin, found that slope and altitude gradients could explain-at least partly-the formation of ecosystem service bundles: provisioning services were concentrated in flat areas (which also had dense cropland, wetland and the largest population density), while regulating services and high levels of biodiversity tended to be distributed in the mountain areas with high forest coverage (Kong et al 2018). Landscape features also influence bundles of demand, since people prioritise or use services based on their interests but also on the landscape's ability to provide them (Hamann et al 2015, Baylan andKaradeniz 2018).…”
Section: Drivers For Ecosystem Services Bundlesmentioning
confidence: 99%
“…Areas with the best agricultural soils were also identified as locations with specialised bundles -for instance, a study in Quebec by Renard et al (2015) showed that good soils were locations of bundles with a low diversity of services and dominated by crop production. Another study, in the Yangtze River Basin, found that slope and altitude gradients could explain-at least partly-the formation of ecosystem service bundles: provisioning services were concentrated in flat areas (which also had dense cropland, wetland and the largest population density), while regulating services and high levels of biodiversity tended to be distributed in the mountain areas with high forest coverage (Kong et al 2018). Landscape features also influence bundles of demand, since people prioritise or use services based on their interests but also on the landscape's ability to provide them (Hamann et al 2015, Baylan andKaradeniz 2018).…”
Section: Drivers For Ecosystem Services Bundlesmentioning
confidence: 99%
“…Among provisioning ES there were positive correlations, suggesting a synergistic relationship, such as the one discussed by Turner et al [14]. Regarding the relationships between provisioning and regulating ES on a diverse landscape, Kong et al [84] found that crop production had a significantly strong negative correlation with soil retention. However, a similar finding was only evident in Lefkada for one year (2015), where cultivated crops showed a moderate trade-off relationship with erosion prevention.…”
Section: Interactions Among Ecosystem Servicesmentioning
confidence: 91%
“…In addition, this bundle in Corfu provided a set of multiple ES (incl. all ES groups) through the years, which contrasted with other agricultural bundles [10,11,84]. In Zakynthos, despite the increase in the tourism industry and population density [40], the agricultural bundle varied across years, but retained a stable extent and supply of Provisioning ES.…”
Section: Interactions Among Ecosystem Servicesmentioning
confidence: 96%
See 1 more Smart Citation
“…With the development of urbanization, a rural revitalization becomes a long-standing challenge and a top priority for the local government in mountainous areas [2,3]. Most scientists and managers agree that the development of tourism industry could boost economic development and improve livelihood, which is a preferred strategy based on the ecological sources and local culture in mountainous areas [4,5]. CES are considered the basis for the tourism industry, while maintaining ecological security and conserving biodiversity also depended on sustainable use of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%